Gender and kidney transplantation - Nautiyal, Arushi; Bagchi, Soumita; Bansal, Shyam Bihari (Frontiers in Nephrology, 2024)
Kidney transplantation provides the best form of kidney replacement therapy with improvement in quality of life and longevity. However, disparity exists in its availability, utilisation and outcomes, not only due to donor availability or financial constraints but also arising from the influence of biological sex and its sociocultural attribute i.e., Gender. Women make up the majority of kidney donors but are less likely to be counselled regarding transpantation, be waitlisted or receive living/deceased donor kidney. Biological differences also contribute to differences in kidney transplantation among the sexes. Women are more likely to be sensitised owing to pregnancy, especially in multiparous individuals, complicating donor compatibility. A heightened immune system in women, evidenced by more autoimmune illnesses, increases the risk of allograft rejection and loss. Differences in the pharmacokinetics of transplant drugs owing to biological variances could also contribute to variability in outcomes. Transgender medicine is also increasingly becoming a relevant topic of study, providing greater challenges in the form of hormonal manipulations and anatomic changes. It is thus important to determine and study transplantation and its nuances in this backdrop to be able to provide relevant sex and gender-specific interventions and design better practices for optimum kidney transplant utilisation and outcomes.